2003
DOI: 10.1017/s0022112003005366
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurements of the normal stresses in sheared Stokesian suspensions

Abstract: We present experimental measurements of the normal stresses in sheared Stokesian suspensions. Though the suspending fluid is Newtonian, dispersing rigid non-Brownian particles in it yields a suspension that is non-Newtonian, as it exhibits normal stress differences and an excess isotropic pressure in viscometric flows. At small to moderate concentrations, the normal stresses are very small in magnitude, and hence difficult to measure. This difficulty is compounded by the presence of noise due to unavoidable ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
92
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 14 publications
17
92
0
Order By: Relevance
“…The second normal stress difference |N 2 | is found to be larger than |N 1 | with N 2 /N 1 ⇡ 3.6. Later measurements by Singh & Nott (2003) using similar devices have confirmed that N 1 and N 2 are both negative but with a ratio N 2 /N 1 which depends on φ. Dai et al (2013) used a combination of a parallelplate rheometer and the open semi-circular trough method to measure N 1 and N 2 .T h e y found a good agreement with previous works with negative normal stress differences and |N 1 |⌧| N 2 |.…”
Section: Introductionmentioning
confidence: 84%
“…The second normal stress difference |N 2 | is found to be larger than |N 1 | with N 2 /N 1 ⇡ 3.6. Later measurements by Singh & Nott (2003) using similar devices have confirmed that N 1 and N 2 are both negative but with a ratio N 2 /N 1 which depends on φ. Dai et al (2013) used a combination of a parallelplate rheometer and the open semi-circular trough method to measure N 1 and N 2 .T h e y found a good agreement with previous works with negative normal stress differences and |N 1 |⌧| N 2 |.…”
Section: Introductionmentioning
confidence: 84%
“…Several previous studies [11][12][13][14][15][16] have attempted to determine parts of the particle phase stress by experiment, simulation, or analysis, by equating ͗ h ͘ p with ⌺ h͑p͒ . In view of our result, their results and interpretations are at least partly in error.…”
Section: Introductionmentioning
confidence: 99%
“…͑1͒-what they actually measured is a part of the suspension pressure. Indeed, Singh and Nott 16 realized that they could not determine the particle phase pressure from rheological measurements of the suspension. The normal stress differences measured by simulation 13,15 and experiment 14,16 are useful viscometric properties of the suspension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these non conventional rheological tools (rotating-rod and tiltedtrough), the value is found too close to zero to determine whether it is negative, positive or null within experimental accuracy. Some experiments using more conventional rheometry find that N 1 is quite small and negative [10][11][12][13], while others report positive values [14]. Some recent studies point to the effect of polydispersity [15] and of confinement [16] which may explain these discrepancies.…”
Section: Suspension Viscositymentioning
confidence: 99%